Right to fair compensation and transparency in, rehabilitation and resettlement act, 2013 - Chakraborty, R. (New Delhi, 2017)
This edition is an analytical, critical and comparative study of the totality of the case law bringing it up to date in lucid and systematic presentation.
Keywords: Eminent domain - India